Caffeinated and decaffeinated coffee consumption and risk of all‐cause mortality: a dose–response meta‐analysis of cohort studies. Issue 3 (20th February 2019) - Li, Q.; Liu, Y.; Sun, X.; Yin, Z.; Li, H.; Cheng, C.; Liu, L.; Zhang, R.; Liu, F.; Zhou, Q.; Wang, C.; Li, L.; et al.
Abstract: Background: Previous meta‐analysis showed an inverse association between coffee consumption and all‐cause mortality. However, the relationship between caffeinated and decaffeinated coffee consumption and all‐cause mortality is inconsistent. We aimed to identify and review the published evidence updating the association between coffee consumption and all‐cause mortality and, furthermore, to investigate the association of caffeinated and decaffeinated coffee consumption and all‐cause mortality. Methods: We systematically searched PubMed and Web of Science for studies published up to 9 November 2017. Cohort studies in which authors reported relative risks (RRs) of all‐cause mortality for at least three levels of coffee consumption were eligible. Random‐effects models were used to estimate the pooled RR of all‐cause mortality with coffee consumption. Restricted cubic splines were used to model the dose–response association. Results: We included 21 cohort study articles (10 103 115 study participants and 240 303 deaths). We found a nonlinear association between coffee consumption and all‐cause mortality ( P nonlinearity < 0.001). Compared with no or rare coffee consumption, with a consumption of 3 cups day –1, the risk of all‐cause mortality might reduce 13% (RR = 0.87; 95% confidence interval = 0.84–0.89). Conclusions: The findings of the present study provide quantitative data suggesting that coffee consumption plays a role in reducing the risk of all‐cause mortality. Similar inverse associations are found for caffeinated coffee and decaffeinated coffee.